Responsabilidade educacional do Estado: a educação para a cidadania - Hajaj, Irene (2006)
This essay broaches State s educacional responsibility, which connects to every human knowledge fields and therefore is incessantly current and recyclabe in the course of history, and in education and the evolution of Man and citizen themselves. It has the aim to connect constitutional s precepts available in articles 205 to 214 in Magna Letter and its (non-) enforcement by Public Power, concerning to current moment in Brazilian reality, and looking at Education by an outside-viewer perspective. We shall broach education and educational system s genesis as doctrine of human behavior, by doing a brief historical digression starting from Classical Period, through Cristian and Modern Periods, and finally reaching the present days. We intend to emphasize educacional differences between Sparta and Athens, and the relation between State and power in those societies, focusing on State s educational responsibility facing both the surrounding world and its citizens, mainly when carrying out administrative functions inherent to the State system. Constitutional precepts inserted in Federal Constitutional of 1988 be related to education and educational process, precepts of those based on social rights and social State s responsibility. Al last we shall deal with citizenship principles and human person s dignity, focused on its historical context and its drill, prospecting possibilities of the construction of that one citizenship to every individual